Marketing Strategy of Starbucks - Kříž, Matyáš (2021)
The thesis focuses on the marketing strategy of Starbucks Coffe Company on the Czech market. The theoretical part is focused on the description of basic concepts like marketing mix and communication mix as well as the history of Starbucks. A questionnaire survey was also conducted with the aim of finding out why customers visit Starbucks stores, if they are aware of its sustainability commitments and whether they are satisfied with its product and loyalty offerings.